THE IMPACT OF DIGITALIZATION ON MSME PRODUCTIVITY IN THE DIGITAL ECONOMY ERA - Dwiansyah, Ipung; Mayasari, Astried Nadia; Jannah, Annisa Huda Muya; Setyanti, Sri Wahyu Lely Hana (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
Purpose – This study aims to comprehensively analyze the effect of digitalization on the productivity of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in the context of the digital economy era. This research is motivated by changes in the business landscape due to the development of digital technology which requires MSMEs to adapt in order to remain competitive. Design/methodology/approach – This research design uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to a representative sample of MSME players in various sectors in Indonesia who have adopted digital technology in their business activities. Data analysis was conducted using regression techniques to test hypotheses regarding the effect of digitalization (measured through the adoption of e-commerce, social media, digital payment systems, and the use of cloud computing) on MSME productivity (measured through increased sales, operational cost efficiency, and market reach). Findings – The research findings show that digitalization has a positive and significant influence on MSME productivity. The adoption of e-commerce and social media significantly increases market reach and sales, while the use of digital payment systems improves transaction efficiency and reduces operational costs. The use of cloud computing was also found to contribute to data management and operational efficiency. Originality/value – The originality/value of this research lies in the comprehensive empirical testing of the different dimensions of digitalization and their influence on various aspects of MSME productivity in Indonesia. This research also provides practical implications for MSMEs in optimizing the use of digital technology and for the government in formulating policies that support the digitalization of MSMEs to improve national economic competitiveness. This research makes an important contribution to the literature on MSME digitalization in Indonesia, and provides guidance for MSMEs to make optimal use of digital technology.